Integrasi Prinsip Keselamatan Kerja dalam Manajemen Proyek Saat Gempa di Yogyakarta Praktik dan Arah Masa Depan - Zainul Faizien Haza; Retno Widiastuti; Khairul Aziz Raihan (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
The objective of this research is to analyze the integration of Occupational Health and Safety (OHS) principles in Project Management during earthquakes in Yogyakarta, both in the present and future. The research method employed in this study is a literature review. The research findings indicate that the implementation of OHS practices in the construction industry can be carried out by all workers involved in the project. However, the execution of OHS measures cannot be avoided in the event of natural disasters such as earthquakes. Seismic-prone areas like Yogyakarta require the integration of effective OHS measures both presently and in the future. Several integrations can be implemented, including the establishment of government regulations that ensure project work is conducted in compliance with standards, encompassing human resources and materials. Additionally, during project implementation, there is a need for socialization programs regarding training and safety in the construction industry and OHS practices. In the construction sector, it is also important to establish evacuation routes or emergency protocols during and after construction. The formation of specialized teams to handle community emergencies in the vicinity of Yogyakarta is crucial. Furthermore, for future integration, it is essential to develop plans and concepts for post-earthquake disaster recovery in the affected regions.